Nonylphenol in Human Breast Milk in Relation to Sociodemographic Variables, Diet, Obstetrics Histories and Lifestyle Habits in a Turkish Population - Sengul SISE; Cevdet UGUZ (Tehran University of Medical Sciences, 2017)
Background: Human breast milk is the most important food for infants and one of the main roads to exposure to toxic substances. In this study, nonylphenol (NP) levels in human milk samples collected from Turkish mothers (n=100) were determined, and the factors including mothers' demographics, eating habits, obstetric histories, and usage of cleaning and cosmetic products were examined. Methods: Participants were mothers of randomly selected infants and toddlers from the Primary Health Care Center Number-8 in Afyonkarahisar City in western Turkey. The concentrations of NP in milk samples were measured using high-performance liquid chromatography (HPLC). Results: All the analyzed samples showed the occurrence of NP at levels up to 47 ng/ml. The mean± SE and the median NP concentrations were 10.1±0.98 ng/ml and 8.46 ng/ml or ppb, respectively. A negative correlation with infant age was observed. There was a significant correlation between fresh fish consumption and the level of NP in the breast milk of mothers. No significant association between body mass index (BMI) and the NP level in human milk of mothers was observed. The mothers who were using excessive cleaning products in comparison to those using less had significantly higher NP in their breast milk. Conclusion: This study provides the first report about NP levels in a population and characterizes individual variation, thus giving a measure of exposed infants through breastfeeding in Turkey.